Neoadjuvant and adjuvant therapy for gastrointestinal stromal tumors - Iwatsuki, Masaaki (Ann Gastroenterol Surg, 2018)
Gastrointestinal stromal tumors (GIST) are rare and mesenchymal in origin with a yearly incidence of 10‐15 cases per million people. If it is technically resectable, surgical resection is the mainstay of therapy regardless of tumor location,. Although complete (R0) resection can be achieved in up to 85% of patients with primary disease, approximately 50% of patients experience recurrence or metastases within 5 years of primary resection. Moreover, prior to 2000, the prognosis of patients with advanced, inoperable GIST was poor because the molecular mechanism had not sufficiently been elucidated, thus effective therapy was lacking. The tyrosine kinase inhibitor imatinib, which selectively inhibits tyrosine kinase KIT, has shown substantial clinical benefit for patients with GIST. In clinical trials, imatinib treatment resulted in response rates of 40%‐55% and longer progression‐free survival for patients with a KIT‐positive unresectable or metastatic GIST. Furthermore, recent clinical trials have shown that giving imatinib after curative resection for high‐risk cases prolonged recurrence‐free survival and overall survival in an adjuvant setting. Several clinical trials of imatinib treatment in a neoadjuvant setting are ongoing; however, in clinical settings, there are problems to resolve, such as optimal agents, duration of administration, and postoperative management. In this review, we discuss the application of surgical options, combined with adjuvant/neoadjuvant or perioperative imatinib treatment and their potential impact on survival for patients with primary, recurrent, or metastatic GIST.